Hospital-Acquired Bloodstream Infections With MRSA and VRE: Standardized Admission Screening Did Not Impact Rates. (October 2020) - Ellison, Jennifer; Chow, Blanda; Howatt, Andrea; Pfister, Ted; Bush, Kathryn
Abstract : Background: Bloodstream infections (BSIs) are an important cause of morbidity and mortality in severely ill patients, contributing to increased length of stay and a higher cost of care. Surveillance of hospital-acquired (HA) BSI is considered a measure of quality of care and has been performed provincially in Alberta since 2011. Prior to October 2015, a nonstandardized, risk-factor–based VRE screening process was used. Screening practices for antibiotic-resistant organisms (AROs) were aligned in October 2015 with a provincially standardized admission screening tool to allow for early initiation of contact precautions for patients colonized or infected with MRSA or VRE. In this data review, we sought to determine whether this admission screening change influenced ARO infections through review of HA-BSI rates. Methods: Prospectively, we reviewed reports of all patients admitted to Alberta Health Services/Covenant Health acute-care and acute-/tertiary-care rehabilitation facilities who met inclusion criteria: (1) positive blood culture identified with MRSA or VRE; (2) new episode for the patient; and (3) positive result occurred on or after calendar day 3 of admission. Data are presented as quarterly rates. Screening practices for MRSA and VRE were standardized provincially in October 2015 to include screening for MRSA on admission for patients who had an inpatient admission, received hemodialysis, or was an inmate in a correctional facility in the past 6 months. We also screened for VRE patients admitted to a solid-organ transplant unit or a hematology unit, regardless of risk factors. Results: We detected no changes in the quarterly rates of HA-BSI with MRSA or VRE after admission screening was standardized. Prior to standardized screening, MRSA BSI rates ranged from 0.12 to 0.25 per 10, 000 patient days, with an overall rate of 0.18 per 10, 000 patient days. After standardization, rates ranged from 0.09 to 0.30 per 10, 000 patient days, with an overall rate of 0.17 per 10, 000 patient days ( P = .46). VRE BSI rates prior to standardization ranged from 0.03 to 0.13 per 10, 000 patient days, with an overall rate of 0.08 per 10, 000 patient days, which increased slightly to 0.09 per 10, 000 patient days after standardized screening, ranging between 0.04 and 0.16 per 10, 000 patient days ( P = .61). Conclusions: Following the implementation of standardized admission screening and the early initiation of contact precautions, no significant changes were observed in rates of either HA-BSI with MRSA or VRE. Further investigation is required to identify the most effective strategies to reduce HA-BSIs caused by MRSA and VRE. Funding: None Disclosures: None